Karakteristik Fisik Formula Nanoliposom Minyak Biji Alpukat (Percea americana Mill): Physical Characteristics of Avocado Seed Oil (Persea americana Mill) Nanoliposome Formulation - Abdul Aziz; Vania, Yoshe; Arina Shaleha, Shinta; Naela Amalia, Berlian; Miftakhur Rohmah, Riska; Sunnah, Istianatus (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Ngudi Waluyo, 2025)
Nanoliposomes are nanoparticle technology that has a topical drug delivery system composed of a phospholipid bilayer membrane. The shape of nanoliposomes can penetrate into the layer intracellularly through the lipid network in the stratum corneum. Avocado seed oil (Persea americana Mill) contains secondary metabolites such as flavonoids, saponins, terpenoids, steroids, tannins and fatty acids that have health benefits so that for optimal use it can be made in nanoliposomes. The purpose of this study was to evaluate the physical characteristics of avocado seed oil nanoliposomes. This research method began with producting avocado seed oil produced from the extraction process by the soxhletation method using n-hexane solvent. Phytochemical screening were carried out qualitatively. Nanoliposomes were made using the thin layer hydration method using 1 lipid bilayer. The physical quality test of nanoliposomes included organoleptic, pH, viscosity, particle size, polydispersity index and transmittance percentage. The results of the physical quality evaluation were presented descriptively. The results of qualitative phytochemical screening showed that avocado seed oil contains flavonoids, saponins, and tannins. The physical characteristics of nanoliposomes are semi-solid, brown in color, distinctive odor, pH 6.68 ± 0.02; viscosity 3.358 ± 130.39 cps, particle size 531.83 ± 12.40 nm; PDI 0.123 ± 0.05. Based on these results, it can be concluded that the physical characteristics of avocado seed oil nanoliposomes meet the requirements, the particle size of the resulting nanoliposomes is included in the category of Large Unilamelar Vesicles and is distributed homogeneously monodisperse. Based on the particle size, the nanoliposomes cannot penetrate the stratum corneum. ABSTRAK Nanoliposom merupakan teknologi nanopartikel yang memiliki sistem penghantaran obat secara topikal yang tersusun oleh membran fosfolipid bilayer. Nanoliposom dapat berpenetrasi ke dalam lapisan secara intraseluler melalui jaringan lipid pada stratum corneum. Minyak biji alpukat (Persea americana Mill) memiliki senyawa metabolit sekunder seperti flavonoid, saponin, terpenoid, steroid, tanin dan asam lemak yang memiliki manfaat untuk kesehatan sehingga untuk optimalisasi penggunaan dibuat bentuk nanoliposom. Tujuan penelitian ini adalah mengevaluasi karakteristik fisik nanoliposom minyak biji alpukat. Metode penelitian dimulai dengan produksi minyak biji alpukat melalui proses ekstraksi dengan metode soxhletasi menggunakan pelarut n-heksan. Skrining fitokimia dilakukan secara kualitatif. Pembuatan nanoliposom menggunakan metode hidrasi lapis tipis menggunakan 1 lipid bilayer. Uji mutu fisik nanoliposom meliputi organoleptis, pH, viskositas, ukuran partikel, indeks polidispersi dan persentase transmittan. Hasil evaluasi mutu fisik disajikan secara deskriptif. Hasil skrining fitokimia secara kualitatif, minyak biji alpukat mengandung flavonoid, saponin, tanin. Karakteristik fisik nanoliposom memiliki bentuk semi padat, warna coklat, bau khas, pH 6,68±0,02; viskositas 3.358±130,39 cps, ukuran partikel 531,83±12,40 nm; PDI 0,123±0,05. Berdasarkan hasil tersebut dapat disimpulkan bahwa karakteristik fisik nanoliposom minyak biji alpukat memenuhi syarat. Ukuran partikel nanoliposom yang dihasilkan termasuk kategori Large Unilamelar Vesicles dan terdistribusi homogen monodispersi. Berdasarkan ukuran partikel sediaan nanoliposome tidak dapat menembus stratum corneum.